Uso de Anfibios como Indicadores del Éxito de la Restauración de Ecosistemas - Ken G. Rice; Frank J. Mazzotti; J. Hardin Waddle; Marianna D. Conill (EDIS, 2007)
Circular 1484-S, a 6-page illustrated fact sheet by Ken G. Rice, Frank J. Mazzotti, J. Hardin Waddle, and Marianna D. Conill, is the Spanish Translation of "Circular 1484: Use of Amphibians as indicators of Ecosystem Restoration Success." It describes research being conducted to evaluate the use of amphibians as indicator species in monitoring the effects of the Everglades Restoration Plan. Includes references.  Published by the UF Department of Wildlife Ecology and Conservation, November 2006.